CuO as a reactive and reusable reagent for the hydrogenation of nitroarenes - Rajendran, K.; Pandurangan, N.; Vinod, C. P.; Khan, Tuhin S.; Gupta, Shelaka; Haider, M. Ali; Jagadeesan, D. (Applied Catalysis B-Environmental, 2021)
{Copper oxide (CuO) is used as a reusable solid reagent for hydrogenation of nitroarenes to aminoarenes. The use of CuO resulted in 100 % conversion of 2.9 mmol of nitrobenzene to aniline in 45 s at room temperature using hydrazine hydrate as the reducing agent. During the reaction, CuO is converted to inactive metallic Cu which can be regenerated to active CuO by thermal oxidation. DFT simulations indicated facile formation of oxygen vacancies (EO
Keywords: Copper vacancy; CuO; Hydrogenation; Nitroarene reduction; Oxygen defects; Reactive solids

Oxidation of ethylene by Cu/TiO2: reducibility of Cu2+ in TiO2 as a possible descriptor of catalytic efficiency - Rajendran, K.; Sharma, Mandeep; Jaison, Augustine; Ankitha, Menon; Tiwari, Ankit D.; Vinod, C. P.; Jagadeesan, Dinesh (Catalysis Science & Technology, 2023)
Catalytic oxidation using non-noble metal-based catalysts is a promising approach to mitigate pollution due to VOCs in the air. In this work, mesoporous Cu/TiO2 catalysts containing different concentrations of Cu2+ (0.2, 1, 3, and 4 wt% Cu w.r.t. Ti) were synthesized using the sol-gel technique. The catalysts were characterized using inductively coupled plasma-optical emission spectrometry, XRD, Raman spectroscopy, N-2 physisorption, cyclic voltammetry, H-2-TPR and electron microscopy to understand the structure and composition. The thermal catalytic gas phase oxidation of ethylene was studied by heating a mixture of ethylene (1.5 vol%) and air (5.9 vol%) in the presence of the Cu/TiO2 samples in the temperature range of 298 to 773 K. Cu/TiO2 showed a higher catalytic activity compared to TiO2 for the thermal oxidation of ethylene, indicating a strong promotion by doped copper ions. A volcanic behaviour in the catalytic activity was observed with different concentrations of Cu doping, with 1% Cu/TiO2 showing a 99.5% ethylene conversion at 673 K and 100% selectivity to CO2. The activity of 1% Cu/TiO2 remained consistent without deactivation for 24 h. At low dopant concentrations of Cu (0.2 and 1% Cu/TiO2), the reduction of Cu2+ to Cu+ was observed. An interplay of oxygen vacancies (O-V), Cu+, Cu2+ and Ti4+ may be involved in controlling the activity. DRIFT studies indicated the formation of surface bidendate carbonate as a possible intermediate.